Reduction in labile plasma iron during treatment with deferasirox, a once-daily oral iron chelator, in heavily iron-overloaded patients with β-thalassaemia - Daar, Shahina (Blackwell Publishing Ltd, 2009)
This subgroup analysis evaluated the effect of once-daily oral deferasirox on labile plasma iron (LPI) levels in patients from the prospective, 1-yr, multicentre ESCALATOR study. Mean baseline liver iron concentration and median serum ferritin levels were 28.6 ± 10.3 mg Fe/g dry weight and 6334 ng/mL respectively, indicating high iron burden despite prior chelation therapy. Baseline LPI levels (0.98 ± 0.82 μmol/L) decreased significantly to 0.12 ± 0.16 μmol/L, 2 h after first deferasirox dose (P=0.0006). Reductions from pre- to post-deferasirox administration were also observed at all other time points. Compared to baseline, there was a significant reduction in preadministration LPI that reached the normal range at week 4 and throughout the remainder of the study (P≤0.02). Pharmacokinetic analysis demonstrated an inverse relationship between preadministration LPI levels and trough deferasirox plasma concentrations. Once-daily dosing with deferasirox ≥20 mg/kg/d provided sustained reduction in LPI levels in these heavily iron-overloaded patients, suggesting 24-h protection from LPI. Deferasirox may therefore reduce unregulated tissue iron loading and prevent further end-organ damage.